Economic Growth and Income Inequality in Sub-Saharan Africa: Does Environmental Policy Matter? - (:unkn) unknown (My University, 2024)
The counter-intuitive correlation between economic growth and income inequality in sub-Saharan Africa in recent years and the lack of consensus in the literature on this relationship call for its re-examination, particularly in the context of sustainable development. This article analyses the effect of environmental policies on the relationship between economic growth and income inequality in sub-Saharan Africa. With its suitability for analyzing non-linear relationships, the panel smooth transition regression model (PSTR) of Gonzalès (2005) was applied to data covering the period 1999 to 2021 from the World Bank, the Yale Center for Environmental Law and Policy (YCELP), the World Governance Indicator (WGI) and the World Income Inequality Database WIID.In the presence of a strict application of environmental policies, the results show a U-inverted relationship between economic growth and income inequality in sub-Saharan Africa. The more a relatively wealthy country adopts a rigorous environmental policy, the more economic growth contributes to reduce income inequalities. Thus, the socially virtuous effect of a rigorous environmental policy only occurs in economically dynamic countries. In other words, environmental policies in sub-Saharan African countries can only be promoted in relation to their economic performance. Any standardisation of environmental policies on a continental or sub-regional scale for economically different countries should be reconsidered.
Keywords: African Research